SAXOPHONE INSTRUMENT ARRANGEMENT BY GRUB SAXOBROTHER IN THE SONG RUNGKAD COVER HAPPY ASMARA - Hermawan, Ivan Chris; M.Sn, Hery Murbianto (APRON Jurnal Pemikiran Seni Pertunjukan, 2024)
Many popular singers have works, one of which is currently popular, the song Rungkad. The song Rungkad has many versions, one of which is sung by Happy Asmara and is currently popular because it is collaborated with the Saxophone instrument. Data regarding the arrangement of melodic variations contained in the Saxophone Instrument Arrangement by Grub Saxobrothers in the song Rungkad Cover Happy Asmara was found using qualitative descriptive research methods. The description stage was carried out by directly observing the saxophone instrument by the saxobrothers group in the rungkad cover song Happy Asmara, namely by describing the findings of the various melodic arrangements used. The data found was then reduced using source triangulation techniques, namely library source triangulation and resource triangulation. Keyword : Arrangement, Rungkad, Melody Variations